The European Green Deal: climate action, social impacts and just transition safeguards - Arabadjieva, K; Bogojević, S (Oxford University Press, 2024)
The European Green Deal (EGD) is a growth strategy that seeks to combine climate action with economic stimuli. Climate action, however, inevitably creates winners and losers, at least in the short term. Zooming in on two examples of such actions—the phase-out of coal in Bulgaria and the mining for lithium (necessary for electric vehicle batteries) in Serbia—we point to the significant social implications of the EGD and how these give rise to conflicts that threaten to undermine the economic transformation envisioned for achieving climate neutrality. We show that the remedies put in place by the EU to deal with the social consequences of climate action are too narrow and fragmented and contain almost no legal obligations to promote a socially ‘just transition’ that ‘leaves no-one behind’—the leitmotif of the EGD. We join forces here, as scholars of labour law and environmental law, to identify substantive and procedural legal safeguards that would strengthen the social element of the EU climate agenda and help mitigate some of the emerging conflicts and backlash against climate policies.